Championing responsibility: 17 remarkable responsible marketing campaigns to inspire change - Harun, Rabitah; Abd Rahman, Nurul Hayani; Shafie, Nani Ilyana (Universiti Teknologi MARA, Kedah, 2024)
Marketers should prioritize the integration of social marketing initiatives and actively participate in community and public engagement. Hence, our marketing students must possess practical proficiency in addressing the prevailing societal issues in Malaysia. Marketers are the group with the highest probability of attending and engaging in social-orientated initiatives. The principal aim is to furnish marketers with a hands-on understanding of contemporary social challenges in Malaysia. The project covers areas such as the environment, health-related behavior, injury prevention, environmental behavior, and community engagement. Responsible marketing promotes activities that benefit the target audience, especially the local community. In order to ensure methodical execution and achieve the intended goals, every project necessitates thorough preparation, which entails adhering to a prescribed sequence of 10 phases. We implemented a total of 17 initiatives between October 2022 and August 2024, involving diverse target groups from various backgrounds, including rural communities, the general public, university students, high school students, primary school students, kindergarten students, and children in Kedah State. We diligently observed the process prior to, during, and after the campaign. Subsequently, we can identify a notable positive change in the target audience’s perception. We utilize social media platforms to consistently communicate messages, monitor audience reactions, and promptly address them. These two-year campaign programs have significantly impacted both aspiring marketers and the general public. Ultimately, this campaign has successfully motivated all segments of the audience by delivering an exceptional experience and leaving a significant and enduring impression.